Densification mechanism of deep low-permeability sandstone reservoir in deltaic depositional setting and its implications for resource development: A case study of the Paleogene reservoirs in Gaoshangpu area of Nanpu sag, China - Wang, Shilin; Yang, Xiran; Lu, Yuanyuan; Su, Peidong; Liu, Dong; Meng, Lingjian; Wang, Qi; Li, Liang; Radwan, Ahmed E. (Frontiers in Earth Science, 2022)
A better understanding of the reservoir densification mechanisms is very important for petroleum exploration and controlling the reservoir quality distribution in low permeable reservoirs. This study aims to perform systematic analysis to study the evolution of different microfacies in a deltaic depositional setting of the Paleogene deep low-permeability Gaoshangpu reservoir, define their genetic mechanism, delineate the dominant facies belts, and define the favorable diagenetic sequences to explore the possibility of high-quality reservoirs to be further explored. To understand the tight genesis of the low-permeability reservoirs, we have analyzed the sedimentological and diagenetic evolution characteristics of various microfacies (i.e., underwater distributary channel, distributary bay, mouth bar and front sheet sand) using core data and physical property analysis of the reservoir sand body. The study revealed that the underwater distributary channel and estuary bar sand body with medium- to fine-grained and poor-medium sorting. The diagenesis is dominated by strong compaction, calcareous, argillaceous cementation and dissolution during stage B in early diagenesis and stage A in middle diagenesis. In the fan delta environment, the weak anti-compaction resistance of low permeability reservoir is mainly due to the large content of plastic particles, finer grain size and medium-poor sorting, with an average porosity reduction rate of 65%. This is a key factor for the densification of reservoirs above 3000m. Comparison among different sandstone microfacies of the deltaic setting show that the sand body of the underwater distributary channel with low shale content has slightly stronger compaction resistance. The porosity reduction is not obvious at the depth of 3000-4000m, but the loss of permeability at this depth section is significant, And the reservoir improvement from later dissolution is most obvious at this depth section. Calcareous cementation is the cause for densification of some mouth bars in early stage and of underwater distributary channel in middle and late stage. Under the influence of strong compaction and calcareous-filling pore throat, the sand body of the mouth bar has been basically densified at 3000m, resulting in limited reservoir transformation from later dissolution.